Carboxylesterase 4A Inhibits the Malignant Biological Behavior of Nasopharyngeal Carcinoma via the PI3K/AKT Pathway - Qiaoli Chen MS; Quanxiang Hao MBBS; Yanping Yang MBBS; Limei Li PhD; Danping Li MS; Ran Zhao MS; Wanqi Wei MBBS; Lixian Deng MBBS; Jiaming Su MBBS; Ziyuan Liang MBBS; Shiyue Tang MS; Yaomin Lu MBBS; et al. (Technology in Cancer Research & Treatment)
Background Carboxylesterase 4A (CES4A) belongs to the member of the carboxylesterase family, yet there has been limited research into its malignant biological behavior in malignant tumors. Here, we aim to investigate the expression, cellular biological functions, and the potential underlying mechanism of CES4A in nasopharyngeal carcinoma (NPC). Method A standardized mean difference (SMD) analysis was used to analyze the dysregulation of CES4A based on the gene expression omnibus (GEO) database. qRT-PCR and immunohistochemical staining (IHC) were used to identify the mRNA and protein levels of CES4A in NPC cell lines and tissues, respectively. CCK-8, colony formation, wound healing and transwell assays were utilized to estimate cellular growth and metastasis, respectively. Western blot was conducted to evaluate the activity of PI3K/AKT signaling pathway. Result Both mRNA and protein expression of CES4A was significantly diminished both in NPC cell lines and primary tumor tissues. Ectopic expression of CES4A restrains the proliferation, colony formation, migration and invasion of NPC. Additionally, KEGG analysis based on GEO data and high-throughput transcriptome sequencing of cell lines all strongly suggested that CES4A was involved in regulating phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway. It was observed that AKT and phosphorylated AKT were remarkably reduced in CES4A overexpressing NPC cells, indicating that PI3K/AKT signaling pathway is hindered by CES4A. Conclusion CES4A expression is silenced in NPC, functioning as a tumor suppressor by negatively modulating the PI3K/AKT signaling pathway.